PREVALENCE OF PRIMARY ALDOSTERONISM AND HYPOKALEMIA IN 5, 100 PATIENTS REFERRED TO A TERTIARY HYPERTENSION UNIT. (April 2021) - Burrello, Jacopo; Monticone, Silvia; Losano, Isabel; Cavaglia', Giovanni; Buffolo, Fabrizio; Tetti, Martina; Covella, Michele; Rabbia, Franco; Veglio, Franco; Pasini, Barbara; Williams, Tracy Ann; Mulatero, Paolo
Abstract : Objective: Primary aldosteronism (PA) was considered a rare disorder almost always associated with hypokalemia. After the introduction of aldosterone-to-renin ratio, the widespread screening of hypertensive patients unveiled a higher prevalence of normokalemic PA, which now represents the prevailing phenotype. Many studies have described the prevalence of hypokalemia in patients with PA, conversely the prevalence of PA in patients with hypokalemia is unknown. In this retrospective observational study, we define the prevalence of hypokalemia in referred patients with hypertension and the prevalence of PA in patients with hypokalemia and hypertension. Design and method: For each patient, medical records were reviewed by three independent reviewers, who were blinded to patients' identification and diagnosis. Hypokalemia was defined for potassium levels lower than 3.7 mmol/L. PA was diagnosed according to the Endocrine Society guideline. Multivariate logistic regression analysis was used to assess the association of hypokalemia and PA with cardiovascular risk indicators. Results: Hypokalemia was present in 15.8% of 5, 100 patients with hypertension whereas 76.9% of these patients were normokalemic. PA prevalence in this cohort was significantly higher than in a cohort of 1, 672 unselected patients with hypertension in primary care from the PATO study (7.8% vs. 5.9%, P = 0.011). The prevalence of PA in patients with hypokalemia was 28.1% and increased with decreasing serum potassium concentrations up to 88.5% of patients with spontaneous hypokalemia and serum potassium concentrations below 2.5 mmol/L. A multivariate regression analysis demonstrated the association of hypokalemia with the occurrence of cardiovascular events independent of PA diagnosis. An association of PA with the occurrence of cardiovascular events and target organ damage independent of hypokalemia was also demonstrated. Conclusions: Our results confirm that PA is a frequent cause of secondary hypertension in patients with hypokalemia and the presence of hypertension and spontaneous hypokalemia are strong indications for a diagnosis of PA. Finally, we show that PA and hypokalemia are associated with an increased risk of cardiovascular events.